Pembelajaran Berbasis Masalah (PBM): Peningkatan Motivasi dan Hasil Belajar Peserta Didik di MTs Negeri 4 Kulon Progo - Suryaningsih, Ambar (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2023)
This study aims to analyze the increase in motivation and learning outcomes of learners using problem-based learning (PBM). This study uses classroom action research methods carried out in two cycles including planning, implementation, observation, and reflection activities. The subjects of the study were students of class XI-A MTs Negeri 4 Kulon Progo. Data collection techniques are carried out by observation, documentation, and tests. Data analysis uses qualitative descriptive analysis techniques. The results showed that the application of problem-based learning can increase the motivation and learning outcomes of students with a percentage increase in motivation and learning outcomes reaching 78.18%. The data obtained for aspects of learning motivation were 78.79% (persevering), 78.69% (tenacious), 84.09% (achievement drive), 76.82% (material hinterland), 77.27% (increased achievement), 77.65% (interest in learning), 77.84% (happy learning), 77.84% (enthusiasm for learning), and 77.27% (responsible).